Satisfaction and Loyalty of NBA Athletes in Solo: Effects of Coach Leadership, Club Management, Coach Psychology, Infrastructure Facilities, and Service Quality - Andes Permadi; Muhammad Nasihul Waffak; Oddie Barnanda Rizky; Dian Pujianto; Bogy Restu Ilahi; Septian Raibowo; Andika Prabowo (UNIB Press, 2022)
This study sought to determine the influence of coach leadership, club management, coach psychology, infrastructure, and service quality on the satisfaction and loyalty of NBA athletes.. This research is qualitative research with a descriptive analysis approach. Methodology : The data collection methods used by researchers were observation, interviews, and documentation. The population of this study was 100 people, and 25 samples were taken from leaders in the basketball team organization in Solo city. Only the basketball organization leaders in the Division I were included as the target population. The option to include a basketball coach in a Solo city was the members of the NBA Division I. Data collection techniques employed questionnaires, and the data analysis techniques utilized PLS-SEM. Structure in the organization of management that included planning, organizing, and investigating the practice of athletes and leaders in the organization, required good behavior and discipline to run according to plan. Findings : It indicates that most respondents considered that the service quality variable indicators were good enough. The mean of the service quality variable was signifying that consumers agreed that the indicators of the service quality variable were good. Contribution and Recommendation : The results of this study can be used as input for basketball club coaches. Fixing itself is related to the leadership style, club management, psychology, supporting facilities and infrastructure, and service quality in the club